ChemInform Abstract: Metal‐ and Reagent‐Free Highly Selective Anodic Cross‐Coupling Reaction of Phenols. Issue 39 (23rd September 2014) - Elsler, Bernd; Schollmeyer, Dieter; Dyballa, Katrin Marie; Franke, Robert; Waldvogel, Siegfried R.
Abstract Boron‐doped diamond electrodes allow the direct anodic cross‐coupling of phenols in hexafluoroisopropanol without using leaving functions or protecting groups.